Analisis Kesiapan Pemerintah Aceh Utara dalam Pemindahan Ibukota dari Kota Lhokseumawe ke Lhoksukon - Masyitah, Liatul; Putri, Annisah (Program Studi Ilmu Politik, Universitas Syiah Kuala, Banda Aceh, 2024)
This research evaluates the readiness of the North Aceh Government to face the relocation of the capital from Lhokseumawe to Lhoksukon, focusing on infrastructure, institutions, human resources, and community support. The approach used is the theory of good governance, emphasizing effective and efficient public service in the context of territorial expansion. This study adopts a descriptive analysis method, collecting primary data through interviews with government officials and secondary data through literature and official documents related to the capital relocation. The research results indicate that the North Aceh government has taken initial steps to prepare for the capital relocation. Basic infrastructure such as buildings, roads, water, and electricity is already present in Lhoksukon, although further development is needed to achieve full success. The government has allocated budgets and adopted accountable planning to achieve good governance in this relocation process. Inhibiting factors include budget limitations, the need to establish new government institutions with supporting facilities, and ongoing conflicts among the community that continue to affect the current situation. Abstrak Penelitian ini mengevaluasi kesiapan Pemerintah Aceh Utara dalam menghadapi pemindahan ibukota dari Kota Lhokseumawe ke Lhoksukon, dengan berfokus pada infrastruktur, kelembagaan, sumber daya manusia, dan dukungan masyarakat. Pendekatan yang digunakan adalah teori good governance, yang menekankan pelayanan publik yang efektif dan efisien dalam konteks pemekaran wilayah. Penelitian ini mengadopsi metode analisis deskriptif dengan pengumpulan data primer melalui wawancara pejabat pemerintah dan data sekunder melalui studi literatur dan dokumen resmi yang berkaitan dengan pemindahan ibukota. Hasil penelitian mengindikasikan bahwa Pemerintah Aceh Utara telah memulai langkah-langkah awal untuk mempersiapkan pemindahan ibukota. Infrastruktur dasar seperti bangunan gedung, jalan, air, dan listrik telah ada di Lhoksukon, meskipun masih memerlukan peningkatan dalam pembangunan untuk mencapai kesuksesan penuh. Pemerintah juga telah mengalokasikan anggaran dan mengadopsi perencanaan yang akuntabel untuk mencapai good governance dalam pemindahan ini. Faktor-faktor penghambat mencakup keterbatasan anggaran, kebutuhan untuk membentuk lembaga-lembaga pemerintahan baru dengan kelengkapan sarana penunjang, serta konflik yang berlanjut antara masyarakat yang masih mempengaruhi situasi saat ini.